Immune and parasitological response in horses infected with gastrointestinal nematodes in the humid tropic of Mexico - González-Garduño, Roberto; Maldonado-Simán, Ema; Torres-Hernández, Glafiro; Ponce Covarrubias, José Luis; Oliva-Hernández, Jorge; Mendoza-de Gives, Pedro (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of the study was to determine the parasitological and immune response in horses naturally re-infected with gastrointestinal nematodes (GIN) after an- thelmintic treatment in the humid tropic of Mexico. The study was conducted in Tenosique, Tabasco, Mexico. A total of 30 horses were sampled monthly for nine months. Fecal samples were obtained to determine the number of nematode eggs per gram (EPG) of feces. Stool cultures were performed to obtain and identify infective larvae (L3) genera. Blood samples were also obtained to determine the packed cell volume (PCV), the total plasma protein (TPP), and the differential leukocyte count (DLC). Serum enzyme-linked immunosorbent assays (ELISA) were performed to determine IgA levels against adult cyathostomins and Strongylus nematode antigen. The analyses considered the age and gender of the horses, and the season (Cold, rainy and dry). The number of EPG and TPP were higher in females (1224 ± 1269 and 7.6 ± 0.6 gdL−1, respectively) than males (623 ± 671 and 7.4 ± 0.5 gdL−1, respectively), and no differences were observed with animal age (p > 0.05). The number of EPG increased in the rainy season. The main nematodes involved were of the subfamily Cyathostominae (97.4%) and to a lesser degree of species Strongylus equinus, S. edentatus, S. vulgaris, and Oxyuris equii. The season affected the leukocytes, neutrophils, and lymphocytes counts but not eosinophils. Variables such as gender, animal age, and environmental conditions are important elements for a diagnosis of GIN and the application of treatments for its control.
Keywords: Cyathostomins; equines; immunoglobulins; parasites; Strongylus.